The Effect of Academic Supervision and Use of Information and Communication Technology Towards the Competence of Islamic Education Teachers of Islamic Education at National High School in Cirebon City - Bambang Firmansyah (Eduvis : Jurnal Manajemen Pendidikan Islam, 2020)
This paper collects information about education as a pillar that forms civilization that is associated with the advancement of information and communication technology and pedagogical competence of teachers is the spearhead of education itself towards the nation's next generation. This research method uses survey methods with quantitative research approaches. The intended survey research is to explain the causal relationship and hypothesis testing. The subjects in this study were Islamic High School Islamic Education Teachers in the city of Cirebon, which amounted to 44 people, because of the small number of population, the authors did not take samples. Data collection methods that the authors use in this study using a questionnaire. The results of hypothesis testing found the analysis of the influence of academic supervision on teacher pedagogical competence reached 0.23% with a significant number 0.595> 0.05. The influence of the use of ICT on teacher pedagogical competence reaches 0.886 and a significant value of 0.000 <0.05 means there is a positive influence. Correlation analysis between academic supervision with the use of ICT by 82.3% and significance 0,000 <0.05 means that a positive relationship is recorded and the effect of academic supervision and the use of ICT together have a significant influence on teacher pedagogical competence of 85.8%, with a magnitude of influence of 0.720 and a significance value of 0,000 <0.05. H0 is rejected and Ha is accepted, which means that there is a significant influence between the dependent variable on the independent variable partially and simultaneously. Abstrak Tulisan ini mengumpulkan informasi tentang pendidikan sebagai pilar pembentuk peradaban yang dikaitkan dengan kemajuan teknologi informasi dan komunikasi serta kompetensi pedagogik guru yang merupakan ujung tombak dari pendidikan itu sendiri terhadap generasi penerus bangsa. Metode penelitian ini menggunakan metode survei dengan pendekatan penelitian kuantitatif. Penelitain survei yang dimaksud adalah bersifat menjelaskan hubungan kausal dan pengujian hipotesis. Subjek dalam penelitian ini adalah Guru Pendidikan Agama Islam SMA Negeri di kota Cirebon yang berjumlah 44 orang, karena sedikitnya jumlah populasi, maka penulis tidak mengambil sampel. Metode pengumpulan data yang penulis gunakan pada penelitian ini dengan menggunakan kuesioner. Hasil pengujian hipotesis ditemukan analisis pengaruh supervisi akademik terhadap kompetensi pedagogik guru mencapai 0.23% dengan angka signifikan 0,595 > 0,05. Pengaruh penggunaan TIK terhadap kompetensi pedagogik guru mencapai 0.886 dan nilai signifikan 0,000 < 0,05 artinya terdapat pengaruh positif. Analisis korelasi antara supervisi akademik dengan penggunaan TIK sebesar 82.3% dan signifikasi 0,000 < 0,05 artinya terdata hubungan positif dan pengaruh supervisi akademik dan penggunaan TIK secara bersama-sama memberikan pengaruh yang signifikan terhadap kompetensi pedagogik guru sebesar 85.8%, dengan besarnya nilai pengaruh 0,720 dan nilai signifikasi 0,000 < 0,05. H0 ditolak dan Ha diterima, yang artinya terdapat pengaruh yang signifikan antara variabel dependen terhadap variabel independen secara parsial dan simultan.